Effects of Ascorbic Acid on Diurnal Variations in Rectal Temperature of Shaver Brown Pullets During the Hot-Dry Season - Ayo, J.O.; Sinkalu, V.O. (International Journal of Poultry Science, 2007)
Experiments were performed with the aims of determining the fluctuation in rectal temperature (RT) of Shaver Brown pullets and the effect of vitamin C or Ascorbic Acid (AA) administration on the fluctuation during the hot-dry season in the Northern Guinea Savannah zone of Nigeria. The RT of 25 experimental and 25 control pullets were measured every hour from 06:00 to 19:00 hours for three days, three days apart, with a standard clinical thermometer. The experimental pullets were individually administered orally with AA in drinking water at the dose of 52 mg kg -1 dissolved in sterile water, while the control pullets were given only normal water, without AA addition. In experimental pullets, the lowest hourly RT of 41.0±0.1 °C was obtained at 06:00 hours, while the highest value of 41.6±0.0 °C was recorded at 14:00 and 15:00 hours (p<0.001). In control pullets, the RT rose significantly from 41.0±0.1 °C at 06:00 hours to maximum values, ranging from 41.5±0.0 °C to 41.8±0.0 °C at 11:00 to 17:00 hours (p<0.001). There was a positive and significant (p<0.05) correlation between hours of the day and RT values in experimental (r = 0.589) and control (r = 0.542) pullets. The overall RT of pullets administered with AA was significantly (p<0.05) lower than that of control pullets (41.3±0.1°C and 41.5±0.1 °C, respectively). The minimum and maximum hourly RTs of experimental pullets were 40.3±0.1 and 42.0±0.0 °C, respectively, while those of control pullets were 40.7±0.1 and 41.9±0.0 °C, respectively (p<0.001). The dry-bulb temperature was negatively correlated with RT in experimental pullets (r = -0.240, p>0.05); but in control pullets, the relationship was positive and significant (r = 0.655, p<0.05). The pullets administered with AA had consistently lower RT values than those of control pullets. It is concluded that AA administration, by modulating the body temperature of pullets during the hot hours of the day, ameliorated the thermally stressful effect of the hot-dry season. This mechanism may be partly responsible for AA-induced enhancement of productivity and health of pullets during the season.